2013
DOI: 10.1248/bpb.b12-01086
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variations in Aprepitant Plasma Pharmacokinetics in Cancer Patients Receiving Cisplatin-Based Chemotherapy for the First Time

Abstract: The pharmacokinetics of aprepitant, a neurokinin-1 receptor antagonist, have not been fully evaluated in clinical settings. The aim of this study was to characterize the plasma pharmacokinetics of aprepitant and reveal their influence of laboratory tests and cytochrome P450 (CYP) 3A5 gene polymorphisms in cancer patients. Forty-four Japanese cancer patients receiving cisplatin-based chemotherapy for the first time following oral aprepitant (125 mg on day 1 and 80 mg on days 2 and 3) were enrolled. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…CGRP at the concentration of 10 −7 M induces complete relaxation of human coronary arteries, while pre-incubation with CGRP 8–37 at the concentration of 10 −6 M causes almost perfectly antagonistic effect 127 . Moreover, 10 −6 M of aprepitant, or about 534.4 ng/mL, is well within or below the plasma concentration in cancer patients who took aprepitant to prevent chemotherapy-induced nausea and vomiting: After taking one 125-mg capsule on day 1 followed by an 80-mg capsule on days 2 and 3 128 , the median and interquartile range of plasma concentration of aprepitant 1 day and 3 days were reported to be 768 ng/mL (592–949) and 915 ng/mL (563–1203), respectively 129 . With these considerations, we believe that our choice of doses are well justified.…”
Section: Methodsmentioning
confidence: 99%
“…CGRP at the concentration of 10 −7 M induces complete relaxation of human coronary arteries, while pre-incubation with CGRP 8–37 at the concentration of 10 −6 M causes almost perfectly antagonistic effect 127 . Moreover, 10 −6 M of aprepitant, or about 534.4 ng/mL, is well within or below the plasma concentration in cancer patients who took aprepitant to prevent chemotherapy-induced nausea and vomiting: After taking one 125-mg capsule on day 1 followed by an 80-mg capsule on days 2 and 3 128 , the median and interquartile range of plasma concentration of aprepitant 1 day and 3 days were reported to be 768 ng/mL (592–949) and 915 ng/mL (563–1203), respectively 129 . With these considerations, we believe that our choice of doses are well justified.…”
Section: Methodsmentioning
confidence: 99%
“…Strategies may include using the lowest effective dose, selecting alternative agents when the risk/benefit ratio for use of a supportive care PIM is too high, and educating patients and caregivers on their potential toxicities. For example, if alternative agents such as NK1 receptor antagonists or serotonin-5-(HT) 3 -receptor antagonists can be used, then these agents should be preferentially considered over agents such as metoclopramide, benzodiazepines, or antipsychotics for emesis prevention [14], as these agents have not been associated with adverse outcomes in older adults [15, 16]. In situations where the use of corticosteroids or diphenhydramine may be necessary, patients and caregivers should be educated regarding the potential side effects and the need for closer monitoring to prevent adverse outcomes such as falls.…”
Section: Discussionmentioning
confidence: 99%
“…A study of aprepitant plasma pharmacokinetics in 44 Japanese cancer patients receiving cisplatin de novo, with oral aprepitant 125 mg administered before chemotherapy on day 1 and aprepitant 80 mg given on days 2 and 3, found that plasma aprepitant exposure was not correlated with age or sex [63]. In contrast, another pharmacokinetic study in a larger sample of 315 Japanese cancer patients reported that age had a mild effect on the oral clearance of aprepitant [64].…”
Section: Special Populationsmentioning
confidence: 98%